Analysis of modified back-line inset feed 1×4 array microstrip antenna for 5.8 GHz frequency band - MD. Fazlul, Hasan; Dayang Azra, Awang Mat (UNIMAS, 2025)
This thesis presented the design and optimization of a compact 1×4 microstrip patch array antenna operating at 5.8 GHz using a modified backline feeding technique. Conventional arrays often suffer from mutual coupling caused by surface currents on the feedline, bulky isolation methods that lower gain, narrow bandwidth, challenging impedance matching, and feedline radiation that degrades polarization purity. The study had three objectives: (i) to design and optimize the array for good impedance matching (S11 ≤ –10 dB) and stable resonance through parameter sweep analysis, (ii) to evaluate and enhance bandwidth, gain, and directivity, and (iii) to investigate polarization purity and side lobe behaviour, targeting cross-polarization < –30 dB and acceptable side lobe levels while assessing the effects of coupling and substrate losses. It was hypothesized that the optimized array would achieve stable broadside radiation, higher gain and directivity than a standard-fed array, reduced mutual coupling through the backline layout, and practical impedance matching across the band. The final design achieved resonance at 5.8 GHz with a measured return loss of –21.947 dB, a VSWR of 1.173, and a –10 dB bandwidth of approximately 5%, confirming excellent matching performance. Experimental results further demonstrated a directivity of 10.29 dBi, improved gain relative to a single patch, and balanced excitation leading to stable radiation patterns. Side lobes were kept within acceptable limits and cross-polarization remained below –30 dB, validating the design approach. Overall, the proposed array successfully met its objectives, delivering a compact, efficient, and polarization-pure solution for WLAN/ISM band applications, with measured performance closely matching theoretical expectations and published benchmarks. Keywords: Microstrip 1x4 Array antenna, 5.8GHz frequency band, Back line feeding, CST studio, Impedance Marching, Mutual coupling,